Occupational therapy and occupational science: building critical and transformative alliances/Terapia ocupacional e ciência ocupacional: construindo alianças críticas e transformadoras - Laliberte Rudman, Debbie Laliberte (Cadernos Brasileiros de Terapia Ocupacional, 2018)
Occupational therapy and science are facing calls for social transformation based on the growing awareness and concern with widening occupational inequities and growing occupational injustices apparent at local and global scales. This paper addresses the potential for occupational therapy and science to form productive, critically-informed alliances that support occupation-based socially transformative work. Although acknowledging the critical turn in occupational science, which has raised awareness of problematics within the discipline and moved scholarship in directions that align with transformative work, there is a need for further radical configuration of the conditions that shape and bound occupational science to optimize its potential as a critical ally. The following five key directions should be considered as means to expand the possibilities in occupational science: deeper engagement with critical and transformative paradigms; challenging dualistic thinking; critically situating and politicizing occupation; addressing the moral and political values energizing scholarship; and questioning the status quo within and outside the discipline.